Analisis Waqf Linked Sukuk Untuk Memberdayakan Tanah Yang Tidak Produktif - Nur Dinah Fauziah; Amalia Tulmafiroh (INAIFAS Press, 2020)
Waqf has a higher flexibility compared to zakat so that the scholars perform ijtihad by developing a form of waqf according to the needs of the times. There are so many donated land in Indonesia, but the quality of empowerment has not been maximized. Given, there are still a lot of abandoned land due to lack of funds and guidance to the managers. The presence of sukuk in 2002 was a breakthrough in the development of the capital market in Indonesia because it became an alternative bond instrument for companies that were a source of external funds. Waqf is defined as the retention of property rights over material objects (al-'ain) for the purpose of providing benefits or benefits (al-manfa'ah). And waqf serves to realize the potential and economic benefits of waqf property for the benefit of worship and to advance the welfare of the people. Meanwhile, a sukuk is a long-term securities based on sharia principles issued by the issuer to sukuk holders which obliges the issuer to pay income to sukuk holders in the form of profit sharing / margin /fee as well as repaying the sukuk at maturity. This research approach is a qualitative approach with a literature approach. To empower unproductive land waqf nadzir waqf in collaboration with financial institutions in Indonesia to turn unproductive land into productive land, such as building hospitals, mosques, madrasas, Islamic boarding schools, roads, and other infrastructure. So that the land becomes more beneficial for all mankind. Wakaf memiliki fleksibilitas lebih tinggi dibandingkan dengan zakat sehingga para ulama berijtihad dengan mengembangkan bentuk wakaf sesuai kebuthan zaman. Tanah wakaf di indonesia begitu banyak tapi belum maksimal kwalitas pemberdayaannya. Mengingat, masih banyak tanah yang terbengkalai karena kekurangan dana serta pembinaan pada para pengelolanya. Kehadiran sukuk pada tahun 2002 merupakan terobosan dalam perkembangan pasar modal di Indonesia karena menjadi alternatif instrumen obligasi bagi perusahaan-perusahaan yang merupakan sumber dana eksternal. Wakaf diartikan sebagai penahanan hak milik atas materi benda (al-‘ain) untuk tujuan menyedekahkan manfaat atau faedahnya (al-manfa’ah). Dan wakaf berfungsi untuk mewujudkan potensi dan manfaat ekonomis harta benda wakaf untuk kepentingan ibadah dan untuk memajukan kesejahteraan umat. Sedangkan Sukuk adalah suatu surat berharga jangka panjang berdasarkan prinsip syariah yang dikeluarkan oleh emiten kepada pemegang sukuk yang mewajibkan emiten untuk membayar pendapatan kepada pemegan sukuk berupa bagi hasil/margin/fee serta membayar kembali dan sukuk pada saat jatuh tempo. Pendekatan penelitian ini adalah pendekatan kualitatif dengan pendekatan literatur. Untuk meberdayakan wakaf tanah yang tidak produktif nadzir wakaf bekerjasama dengan lembaga keuangan di indonesia untuk menjadikan tanah yang tidak produktif menjadi tanah yang produktif seperti pembanguna rumah sakit, masjid, madrasah, pesantren, jalan, dan untuk infrastruktur lainnya. Sehingga tanah tersebut menjadi lebih bermanfaat bagi semua umat manusia.